The evolution and function of the Pax/Six regulatory network in sponges. Issue 3 (23rd April 2013) - Rivera, A.; Winters, I.; Rued, A.; Ding, S.; Posfai, D.; Cieniewicz, B.; Cameron, K.; Gentile, L.; Hill, A.
SUMMARY Examining the origins of highly conserved gene regulatory networks (GRNs) will inform our understanding of the evolution of animal body plans. Sponges are believed to be the most ancient extant metazoan lineage, and as such, hold clues about the evolution of genetic programs deployed in animal development. We used the emerging freshwater sponge model, Ephydatia muelleri, to study the evolutionary origins of the Pax/Six/Eya/Dac (PSED) GRN. Orthologs to Pax and Six family members are present in E. muelleri and are expressed in endothelial cells lining the canal system as well as cells in the choanoderm. Knockdown of EmPaxB and EmSix1/2 by RNAi resulted in defects to the canal systems. We further show that PaxB may be in a regulatory relationship with Six1/2 in E. muelleri, thus demonstrating that a component of the PSED network was present early in metazoan evolution.